Parisara: A Free, Public Domain Knowledge Resource on Indian Environment Developed in a Collaborative Fashion - Gadgil, Madhav (JOURNAL OF INDIAN EDUCATION, 2012)
To address the important challenge of taking good care of India’s environment, we clearly need substantial, good quality information. Unfortunately, pertinent information is in very short supply. Most of it is collected through the state machinery, and is of poor quality and highly incomplete. This is because the official machinery violates the spirit of science by discouraging scrutiny. Modern science has abundantly demonstrated that good information flows from an open, transparent process that welcomes participation from all interested parties. We obviously need to put in place such a broad/based, open, participatory process to develop a sound, comprehensive base of information on India’s environment. All over the world, citizens are a great repository of detailed information on many facets of their local environment. Our citizens, especially students and teachers, ought therefore to play an important role in this process of building up a good information resource on India’s environment. The rapidly advancing tools of ICT hold much promise in facilitating such a participatory process of knowledge generation. An outstanding example of such an application is Wikipedia, the free encyclopedia that anyone can edit. Wikipedia articles are expected to be encyclopedic, i.e. based on published, authenticated information, and not on primary observations. Thus, a review of published information on birds of Ratnagiri/Sindhudurg district can, while a checklist of birds of a particular college campus based on personal observations cannot, qualify for an article in Wikipedia. However, the Wiki software is freely available for other users to create their own websites. Therefore, such a checklist could be-hosted on a wiki site set up on the website of a school/college, or some other appropriate agency.